2001
DOI: 10.1038/sj.gt.3301491
|View full text |Cite
|
Sign up to set email alerts
|

Safety of a GM-CSF adjuvant-plasmid DNA malaria vaccine

Abstract: MuStDO 5 is a multivalent plasmid DNA vaccine for malaria comprised of five plasmid DNAs encoding five proteins from Plasmodium falciparum and one plasmid DNA encoding human GM-CSF. To evaluate the safety of MuStDO 5, a series of pre-clinical studies were conducted in mice and rabbits. In pharmacology studies in mice, GM-CSF could not be detected in the serum following either intramuscular or a combined intramuscular/intradermal administration of the vaccine, but was readily detected in the muscle following

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 46 publications
1
30
0
Order By: Relevance
“…[23][24][25] Many strategies have been used in an attempt to enhance the immunogenicity of DNA vaccines. [26][27][28][29][30][31] It is evident that the potencies of these vaccines depends on amount of the antigen expressed in transfected cells. 6 Therefore, a successful DNA vaccine strategy requires both the efficient delivery of DNA into somatic cells and the appropriate expression of the gene products in the targeted cells.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] Many strategies have been used in an attempt to enhance the immunogenicity of DNA vaccines. [26][27][28][29][30][31] It is evident that the potencies of these vaccines depends on amount of the antigen expressed in transfected cells. 6 Therefore, a successful DNA vaccine strategy requires both the efficient delivery of DNA into somatic cells and the appropriate expression of the gene products in the targeted cells.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmid DNA vaccines have been shown to elicit potent humoral and cellular immune responses in a variety of experimental animal models, but the mechanism of immune priming by DNA vaccines remains poorly understood [1][2][3][4][5][6][7]. Following intramuscular injection of a plasmid DNA vaccine, most antigen expression occurs in transfected myocytes at the site of inoculation [1].…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratories and others have demonstrated that the addition of plasmids expressing cytokines and immunomodulatory molecules can substantially augment DNA vaccine-elicited immune responses in both mice and nonhuman primates (3,4,15,16,21,34,37). However, the practical requirements of manufacturing and establishing the safety of the plasmid cytokines prior to the initiation of clinical trials may prove a limitation of this strategy (7,26). Other approaches involve the addition of polymer adjuvants (29) and the use of in vivo electroporation techniques (24,35).…”
mentioning
confidence: 99%